"We are all Here to Stay"; Addressing Aboriginal Title Claims after Delgamuukw v British Columbia - Yurkowski, Rachel A (Victoria University of Wellington Law Review, 2000)
This article outlines how the Canadian courts dealt with the interface between aboriginal title and common law notions of property throughout the various Delgamuukw decisions. Through examination of the different judgments in the case, at different judicial levels, the article traverses issues around the source of aboriginal title, and subsequent limitations on the content of aboriginal title which arise from that. The article concludes that the unique concept of aboriginal title cannot be interpreted within the paradigm of the common law. The article further concludes that courts are the wrong forum for adjudicating aboriginal claims.